DIVERSIFIKASI BUDAYA DALAM PENINGKATAN MUTU LULUSAN PONDOK PESANTREN - Imron Rosady (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2022)
Islamic boarding schools continue to develop continuously in the management of inputs, processes, and outputs to the outcome of the competitiveness of graduates due to their salaf features. This article describes initiatives to vary educational standards in order to boost the employability Islamic Boarding School graduates in Indonesia. Data from documentation are collected for this qualitative library research type. The study's conclusions show that efforts to improve graduates' competitiveness through diversifying the quality of education start with the merger of institutions overseen vision. The integration of students' academic quality was then established using three high-quality coaching models, including coaching in recitations, extracurriculars, and activities in a boarding school setting.